Analisis Tingkat Keterampilan Servis Atas Pada Siswa/Siswi Ekstrakurikuler Bola Voli Di Mts Negeri 01 Kabupaten Lebong - Apriyanto, Sony; Perdima, Feby Elra; Sumantri, Ajis (Journal Of Dehasen Educational Review, 2023)
Volleyball is a team net game that is fun, interesting, and doesn't require a lot of money to play. Volleyball game is played by two teams, each team has six players. Volleyball games can be played both inside and outside the field. The goal of playing volleyball is to keep the ball moving over a high net from one area to the opponent's area. The research method used in this research is descriptive research. The research method used in this study is a survey with a test. This research is a study conducted on independent variables, namely without making comparisons or connecting with other variables. The variable in this study is a single variable, namely the level of service skills in playing volleyball. The skill level of playing volleyball is the degree of consistent success in achieving a goal effectively and efficiently by students. In volleyball skills which consist of service, underpass, upper pass, smash and block. The research sample used was 30 students who took part in extracurricular activities at MTS Negeri 01 Lebong Regency. The results of this study To measure the ability to serve on volleyball extracurricular students at MTS Negeri 01 Lebong, a service test was carried out on 30 samples. The highest score is 25, the lowest score is 11, the mean is 17.63, the median is 18.5, the mode is 19 and the standard deviation is 4.08. The results of the analysis of the data obtained from the over serve test data on volleyball extracurricular students at MTS Negeri 01 Lebong obtained that the most over serve test results were in the medium category with an average of 17.63. The ability to serve volleyball extracurricular students at MTS Negeri 01 Lebong which is in the very good category is 3 people (10%), good category is 6 people (20%), and the medium category is 10 people (33%), and the poor category is 10 people ( 33%), and the very poor category is 1 person (4%). Based on the results of this study, it shows that the service ability of the volleyball extracurricular students at MTS Negeri 01 Lebong. Overall is in the medium category. This situation shows that the level of top serve ability can be a capital to play volleyball well.